INFORMI: A Rasch-Validated Four-Tier Instrument to Diagnose Students’ Conceptions of Momentum and Impulse (Journal of Science Learning, 2026)
This study aims to develop and validate the Instruments of Four-tier Multi-representational on Momentum and Impulse (INFORMI) as a diagnostic instrument to analyze students’ conceptions in physics. The instrument was developed using the ADDIE model, which involves the stages of analysis, design, development, implementation, and evaluation. INFORMI consists of 19 items with four structured tiers: conceptual knowledge, confidence level, reasoning, and reasoning confidence. The instrument was administered to 37 eleventh-grade students at one of the Senior High Schools in Indramayu, Indonesia. Rasch analysis using MINISTEP software was conducted to evaluate the instrument’s psychometric properties. The results indicated that the the instrument fulfilled the requirement for construct validity (30%) and that all items met the fit criteria, with Outfit MNSQ values ranging from 0.60 to 1.46. The item reliability reached 0.86, and the Cronbach’s alpha was 0.62, suggesting adequate internal consistency. The distribution of item difficulty ranged from very easy to very difficult, and all discrimination indices were positive, indicating the effectiveness of each item in distinguishing students’ conceptual understanding. Analysis of student responses revealed that most students fell into the Understands Concept (UC) and partially understands (PU) categories. The findings demonstrate that INFORMI is a valid, reliable, and effective tool for identifying students’ misconceptions in the topic of momentum and impulse. It is recommended that teachers utilize INFORMI as a diagnostic instrument to inform and improve instructional strategies in physics learning.